Spiritual Counseling Grounded in Buya Hamka’s Tazkiyatun an-Nafs: Relevance and Implementation in the Context of Psychological Issues - Yandri, Hengki; Juliawati, Dosi (Indonesian Journal of Counseling and Development, 2025)
The escalating prevalence of psychological issues in modern society underscores the need for counseling approaches that transcend purely rational and behavioral strategies to encompass the spiritual dimension of human experience. This article aims to conceptualize a foundational model of spiritual counseling rooted in Buya Hamka's Tazkiyatun an-Nafs framework, presenting an integrative alternative deeply embedded in local values. Employing a qualitative-conceptual approach, this study proposes a three-phase counseling structure: pre-counseling, core process, and post-counseling. This model integrates the principles of Takhalli (purifying the heart from negative influences), Tahalli (adorning the heart with positive values), and Tajalli (guiding individuals to rediscover deeper meaning and purpose in life). The model emphasizes counseling as a process of spiritual recovery aimed at alleviating psychological problems, facilitated through personalized, reflective, and transformative guidance. While conceptual, this article significantly contributes to the contextualization of Islamic counseling and lays the groundwork for future empirical research.